INTERNALISASI NILAI-NILAI PENDIDIKAN MULTIKULTURAL DI LINGKUNGAN PONDOK PESANTREN ARDANIAH KOTA SERANG - Safitri, Dian; Bahrudin, Febrian Alwan; Fitrayadi, Dinar Sugiana (Universitas Muria Kudus, 2024)
This research was carried out to 1) describe the internalization process of multicultural education values at Ardaniah Islamic Boarding School Serang City, and 2) find out how was the result of value internalization of multicultural education at Ardaniah Islamic Boarding School Serang City. This research employed qualitative approach with descriptive method. The data collection techniques used were interview, observation, and documentation. The data analysis technique was carried out through the stages of data collection, data reduction, data presentation, and taking conclusion. The research results showed that the internalization process of multicultural education at Ardaniah Islamic Boarding School Serang was carried out through the activity of studying the yellow book, there was role of Islamic Scholar (Kyai), and Ustadz-Ustadzah, and through various students’ activities which trigger them to implement the values internalized until obtained that the students can understand the multicultural values, capable of implementing them, and in the end they can become the personality that can be in line with the values of multicultural education.